2009
DOI: 10.1158/1940-6207.capr-08-0086
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-Associated Serum and Colon Markers as Indicators of Dietary Attenuation of Colon Carcinogenesis in ob/ob Mice

Abstract: Although inflammatory cytokines and obesity-associated serum proteins have been reported as biomarkers of colorectal adenoma risk in humans, little is known of biomarkers of response to interventions that attenuate tumorigenesis. Dietary navy beans and their fractions attenuate colon carcinogenesis in carcinogen-induced genetically obese mice. We hypothesized that this attenuation would be associated with changes in inflammatory cytokines and obesity-related serum proteins that may serve as measures of efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…Recent studies have suggested that obesity facilitates colon tumor formation in adiponectin-gene-deficient mice, 34 APC-genedeficient mice 35 and leptin-gene-deficient mice. 36 However, animal models of specific gene-deficient mice may exhibit different molecular mechanisms for developing tumors from those observed in diet-induced obesity. For example, leptin-gene-deficient mice had significantly higher circulating concentrations of inflammatory cytokines, which Obesity accelerates colon carcinogenesis S-Y Park et al may be related to the colon carcinogenesis without involving leptin, 36 whereas our diet-induced obesity created hyperleptinemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that obesity facilitates colon tumor formation in adiponectin-gene-deficient mice, 34 APC-genedeficient mice 35 and leptin-gene-deficient mice. 36 However, animal models of specific gene-deficient mice may exhibit different molecular mechanisms for developing tumors from those observed in diet-induced obesity. For example, leptin-gene-deficient mice had significantly higher circulating concentrations of inflammatory cytokines, which Obesity accelerates colon carcinogenesis S-Y Park et al may be related to the colon carcinogenesis without involving leptin, 36 whereas our diet-induced obesity created hyperleptinemia.…”
Section: Discussionmentioning
confidence: 99%
“…36 However, animal models of specific gene-deficient mice may exhibit different molecular mechanisms for developing tumors from those observed in diet-induced obesity. For example, leptin-gene-deficient mice had significantly higher circulating concentrations of inflammatory cytokines, which Obesity accelerates colon carcinogenesis S-Y Park et al may be related to the colon carcinogenesis without involving leptin, 36 whereas our diet-induced obesity created hyperleptinemia. Therefore, we developed the obese colon cancer model using wild-type animals to study the relationship between diet-induced obesity and colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…57 The researchers attributed this observation to the fact that consumption of the bean diet resulted in considerably lower serum levels of IL-6. Treatment of leptin-receptor-deficient Lepr db/db mice with the ch olesterol-lowering drug pitavastatin resulted in decreased levels of circulating inflammatory cytokines, as well as reduced tumour initiation.…”
Section: Obesity-related Inflammationmentioning
confidence: 99%
“…Supporting a role for diet-induced obesity (DIO) in promoting inflammation and cancer, levels of IL-6 and tumor burden are both reduced following azoxymethane treatment of obese Lep ob / ob mice fed a bean-based diet versus a standard diet (5). Furthermore, medications used to treat hyperlipidemia and hypertension prevent colorectal carcinogenesis by attenuating chronic inflammation (6).…”
Section: Introductionmentioning
confidence: 99%